Partycypacja wyborcza w wyborach samorządowych w Polsce w 2024 roku w kontekście deklaracji udziału w wyborach prezydenckich w 2025 roku wśród najmłodszego elektoratu Małopolski na podstawie badań ankietowych – analiza porównawcza ………. 181 - Olech, Hanna; Nagórzańska, Justyna (Wybory prezydenckie w Polsce w 2025 roku w świadomości najmłodszego elektoratu województwa małopolskiego, 2025)
VOTER TURNOUT IN LOCAL ELECTIONS IN POLAND IN 2024 IN THE CONTEXT OF THE DECLARATION OF ELECTION PARTICIPATION IN PRESIDENTIAL ELECTIONS IN 2025 AMONG YOUNGEST ELECTORATE OF MAŁOPOLSKA BASED ON SURVEY RESEARCH – COMPARATIVE ANALYSISThe purpose of this chapter, which contains the self-reflection of the authors who are representatives of the young electorate, was to compare the turnout in local elections in Poland in 2024 with the declaration of participation in the presidential elections in Poland in 2025 by the youngest electorate of the Małopolska province. Attention was also drawn to the voting turnout of the surveyed electorate in comparison to the nationwide level. Based on the survey conducted among students from selected Małopolska high schools in both 2024 and 2025, a certain trend can be established. A clear trend of interest in the elections among the youngest electorate is becoming more pronounced, which may be influenced by the mediatization of politics and the presence of candidates in the social media space. It is worth noting that the youngest electorate in Małopolska was significantly more active in the 2024 local elections compared to the same group of voters nationwide, which is not confirmed in the 2025 presidential elections.